Addicted To Online Games Among Teenagers And Their Implication for Counseling Service - Nora Astrina Vera; Netrawati Netrawati (Jurnal Neo Konseling, 2019)
Online games is one of the internet-connected games that are in demand starting from children, online games user should be able to think precisely and logically and must be able to place and accept the functions of online gaming facilities. This 1) describe online gaming addication which is seen from the quality of compulsive or encouragement to do continuously 2) describe online games addication as seen from the quality of withdrawal 3) describe online games addication as seen from tolerace quality 4) describe onlien games addication as seen from the quality of interpersonal and health problem.The population of this study was students of SMAN One Batang Kapas 442. The sampling technique used was stratified random sampling so that a sample of 81 students was obtained. The instrument used is an online games addication 1) cmpulsive or encouragement in the high category whith an average achievement of 70,4% whith a total of 57 people 2)whitdrawal is in the high category whith an average achievement of43,2% whith a total of 35 peopel 3)tolerance is at high category with an average achievement of 59,3% with 48 students 4)interpersonal relation an health problems are in the high category with an average achievement of 93,8% with a total of 76 tudents.